PENERAPAN MODEL PEMBELAJARAN TREFFINGER UNTUK MENINGKATKAN KREATIVITAS DAN KEMAMPUAN MENULIS TEKS DESKRIPSI (Studi pada Mata Pelajaran Bahasa SMP Negeri 6 Lahat) - Eka Trisna Juniar; Johanes Sapri (UNIB Press, 2020)
This study aimed to: (1) describe the application of treffinger model to improve students’ creativity skills. (2) describe the application of treffinger model to improve description writing skills students. This study was carry out using Classroom Action Research (CAR) and quasi-experiment. The subject was VII.3 of SMPN 6 Unggul Lahat as a Classroom Action Research class. The VII.1 as experiment and VII.4 as control class.To collect data, researcherused observation sheets to measure the ability of teachers applying treffinger model and students’ creativity skills, as well as tests to measure improvement in description writing. To analyze data, researcher used an average score analyze and t-test. Based on the results of this research concluded that the application of terffinger model can improve student’ creativity and description writing skills students